2019
DOI: 10.1101/780304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell transcriptome profiling of the human alcohol-dependent brain

Abstract: BackgroundAlcoholism remains a prevalent health concern throughout the world. Previous studies have identified transcriptomic patterns in the brain associated with alcohol dependence in both humans and animal models.But none of these studies have systematically investigated expression within the unique cell types present in the brain. ResultsWe utilized single nucleus RNA sequencing (snRNA-seq) to examine the transcriptomes of over 16,000 nuclei isolated from prefrontal cortex of alcoholic and control individu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 49 publications
4
25
0
Order By: Relevance
“…In the present study, we report TLR9 co-expression with microglia as well as astrocytes and neurons, consistent with previous studies reporting colocalization of TLR2, TLR3, and TLR4 with neurons in the postmortem human brain (Casula et al, 2011;Crews et al, 2013;Maroso et al, 2010;Zurolo et al, 2011). All TLRs, except TLR3, signal through the TLR adaptor protein MyD88, which is expressed across cell types but is particularly enriched in microglia and astrocytes (Brenner et al, 2020;Soreq et al, 2017). Alcohol releases HMGB1 from neurons and microglia (Crews et al, 2013;Lawrimore & Crews, 2017), and we find HMGB1 is positively correlated with all induced TLRs except TLR3.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we report TLR9 co-expression with microglia as well as astrocytes and neurons, consistent with previous studies reporting colocalization of TLR2, TLR3, and TLR4 with neurons in the postmortem human brain (Casula et al, 2011;Crews et al, 2013;Maroso et al, 2010;Zurolo et al, 2011). All TLRs, except TLR3, signal through the TLR adaptor protein MyD88, which is expressed across cell types but is particularly enriched in microglia and astrocytes (Brenner et al, 2020;Soreq et al, 2017). Alcohol releases HMGB1 from neurons and microglia (Crews et al, 2013;Lawrimore & Crews, 2017), and we find HMGB1 is positively correlated with all induced TLRs except TLR3.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study to report upregulation of a broad number of frontal cortical genes involved in HMGB1-TLR-MyD88-NFκB cytokine and chemokine neuroimmune cascades in and extend prefrontal cortex AUD transcriptome studies (Brenner et al, 2020) as well as molecular and histochemical assessments of proinflammatory neuroimmune induction in the AUD brain (Crews et al, 2013;Qin & Crews, 2012b). We report that AUD induces gene expression of HMGB1 as well as multiple TLRs (i.e., TLRs 2-9), but not TLR1.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Brenner et al, 2020 79 . snRNA-seq data from the prefrontal cortex of alcoholic and control individuals was obtained from GEO (GSE141552).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have identified a role of immune signaling in AUD pathology. Transcriptomic studies in both human postmortem brain and chronic ethanol treatments in mice find induction and dysregulation of pro-inflammatory signaling pathways (Brenner et al, 2019;McCarthy et al, 2018). This pro-inflammatory activation might contribute to cellular and synaptic pathology as well as behavioral phenotypes associated with AUD (Warden et al, 2020).…”
Section: Introductionmentioning
confidence: 99%